2012
DOI: 10.1089/fpd.2011.0988
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Current Molecular Approaches for Genotyping ofCampylobacter jejuniStrains

Abstract: Campylobacter jejuni has been recognized as the most common bacterial cause of gastroenteritis worldwide, in both developed and developing countries, since the late 1970s. A number of genotyping schemes have been developed to identify the sources and route of transmission of these foodborne pathogens so that proper control measures can be developed. In this review, we provide current genotypic schemes developed for Campylobacter spp. (particularly C. jejuni) over the last decades, along with an evaluation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 137 publications
0
20
0
5
Order By: Relevance
“…In this study, the results showed a distinct association between fla-SVR alleles and RFLP-PCR profiles for both C. jejuni and C. coli isolates. It has been reported that flaA gene based typing methods are not suitable for long-term epidemiological studies due to possible intra-and inter-genomic recombination between flagellin genes, but is a useful tool for Campylobacter genotyping, particularly initial screening of Campylobacter isolates [15,17,18,43] . Similarly, the results indicated that fla-SVR typing alone or in combination with other PCRbased methods can be used preliminary screening of campylobacter isolates in epidemiological studies.…”
Section: Aslantaşmentioning
confidence: 99%
“…In this study, the results showed a distinct association between fla-SVR alleles and RFLP-PCR profiles for both C. jejuni and C. coli isolates. It has been reported that flaA gene based typing methods are not suitable for long-term epidemiological studies due to possible intra-and inter-genomic recombination between flagellin genes, but is a useful tool for Campylobacter genotyping, particularly initial screening of Campylobacter isolates [15,17,18,43] . Similarly, the results indicated that fla-SVR typing alone or in combination with other PCRbased methods can be used preliminary screening of campylobacter isolates in epidemiological studies.…”
Section: Aslantaşmentioning
confidence: 99%
“…A variety of subtyping methods are available for Campylobacter, with the most widely used being multilocus sequence typing (MLST) (4) and pulsed-field gel electrophoresis (PFGE) (5). Neither of these techniques is particularly rapid, with analysis times of several days (6,7). Data processing can also be complex (7,8).…”
mentioning
confidence: 99%
“…Tradicionalmente, el diagnóstico y confirmación de las especies de Campylobacter se ha realizado mediante cultivo bacteriológico y pruebas bioquímicas (Ewnetu y Mihret, 2010;Tadesse et al, 2011;Zaidi et al, 2012); sin embargo, en los últimos años, se han implementado técnicas moleculares como la reacción en cadena de la polimerasa (PCR) (Osail et al, 2012) y técnicas de genotipificación (Frederick y Huda, 2011, Ahmed et al, 2012Abley et al, 2012;Eberle y Kiess, 2012).…”
Section: Introductionunclassified